2022
DOI: 10.21062/mft.2022.049
|View full text |Cite
|
Sign up to set email alerts
|

CoCrFeNiTi High Entropy Alloy Prepared via Mechanical Alloying and Spark Plasma Sintering

Abstract: Mechanical alloying and subsequent compaction with spark plasma sintering was chosen for the fabrication of investigated CoCrFeNiTi alloy method. The alloy was characterized in terms of chemical and phase composition with X-ray fluorescence spectroscopy and X-ray diffraction spectrometry, respectively. The microstructure was examined using light microscopy and scanning electron microscopy equipped with an energy dispersion spectrometer. The alloy showed an ultra-fine grained uniform microstructure composed mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This happens via in-situ reactions during the consequential compaction via SPS. This behaviour has been reported also in previous works [1][2][3][4][5][6], among which the direct contact of the alloy with the graphite die walls is also having a significant role. However, as we are aware, the carbides are homogeneously dispersed throughout the entire crosssection of the compacted alloy favouring the origin of C contamination arising from the PCA.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This happens via in-situ reactions during the consequential compaction via SPS. This behaviour has been reported also in previous works [1][2][3][4][5][6], among which the direct contact of the alloy with the graphite die walls is also having a significant role. However, as we are aware, the carbides are homogeneously dispersed throughout the entire crosssection of the compacted alloy favouring the origin of C contamination arising from the PCA.…”
Section: Introductionsupporting
confidence: 86%
“…The CoCrFeNiMn alloy belongs to the most widely investigated, although it has been almost exclusively prepared either by induction casting or by arc-melting methods, both generating rather coarse-grained microstructures, showing significant heterogeneity. On the other hand, mechanical alloying is fairly used for the preparation of HEAs, except in some of our previous works [2][3][4][5]7]. Among that, the corrosion resistance, either in the aqueous or dry environment, has been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the hardness measuring indicated an increase in both HEAs with the increase in the sintering temperature, and simultaneously, an increase in the apparent density, reaching values close to the theoretical densities. Microcracks caused by the indenter were observed for the samples sintered at 975 • C. P. Kratochvil and F. Prusa [20] produced a near-equiatomic CoCrFeNiTi HEA via mechanical alloying for a total of 10 h and 30 min at 400 RPM, and compacted the metallic powder via SPS at 48 MPa and 1000 • C for 1 min, followed by rapid cooling for 9 min, resulting in a value of 757 ± 18 HV 30. As the authors observed, a good value of compressing strength was obtained (1340 MPa) with no plastic deformation, which indicated a brittle behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…In order to establish the final sintering parameters for the magnetron sputtering targets, in correlation with other experimentations from the literature [20,21] and adjusted for the present research, several tests were carried out by varying the sintering temperature from 800 • C to 975 • C, with the other parameters remaining constant: a pressure of 50 MPa, a heating/cooling rate of 50 • C/min and a dwell time of 5 min.…”
Section: Average Particle Sizementioning
confidence: 99%